Étude sémiotique du discours poétique Les Voix de l’aube de Babacar Sall - Yagué Vahi (OpenEdition, 2014)
This paper proposes an application of Michael Riffaterre’s theory to the collection of poems Les Voix de l’aube (2001) by the Senegalese poet Babacar Sall. Our approach consists of four phases. First, we thought it useful to explain the principal aspects of Riffaterrian stylistics which we have used. Then, we have exploited the central notion of ungrammaticality in the poem of B. Sall. The third section deals with one of the hypogram’s transformation rules, namely, over-determination, while the last part is devoted to another of its rules, conversion. Our objective has been to demonstrate that the text’s semiotic device revealed by Mr. Riffaterre’s stylistic analysis participates in the « text production » and therefore in its « significance » in the sense understood by the theorist.